2010
DOI: 10.1590/s0100-736x2010000400012
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features and vascularization study of caprine cyclic corpus luteum

Abstract: RESUMO.-[Características morfológicas e estudo da vascularização do corpo lúteo cíclico de cabras ao longo do ciclo estral.] O corpo lúteo é uma glândula endócrina temporária que regula tanto o ciclo estral quanto a prenhez, apresentando extrema dependência de aporte sanguíneo adequado. Objetivaram-se avaliar mudanças morfométricas dos ovários e densidade vascular (DV) dos corpos lúteos (CL) de cabras ao longo do ciclo estral (AOLC). Vinte animais foram submetidos ao tratamento para indução/sincronização do es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The decrease in P 4 secretion coincided with a reduction of vascular density on day 16 p.o. Similar results were previously provided for goats, cows and buffaloes (Moura et al, 2003;Papa et al, 2007;Miranda-Moura et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The decrease in P 4 secretion coincided with a reduction of vascular density on day 16 p.o. Similar results were previously provided for goats, cows and buffaloes (Moura et al, 2003;Papa et al, 2007;Miranda-Moura et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Statistical analysis revealed that weight, length and width of the corpora lutea were also significantly affected by the estrous cycle phase (P<0.001, Table 3). The above result has been expected since the measurements of the organ frequently estimate the stage of the estrous cycle and the luteal functional activity (Ferreria-Dias et al, 2006;Papa et al, 2007;Nascimento et al, 2003;Miranda-Moura et al, 2010). Current rates were once again higher when compared to the diameter and volume of peccaries´ CL described by Mayor et al (2006a), perhaps due to the difference in the diet's energy rates taken by the animals favoring weight gain and thus their reproduction.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Curiously we have not found corpora albicantia in any of the ovary examined. CA are described as white fibrous tissue that replaces the regressing corpus luteum approximately equal to 3-4 mm in diameter in ewes (28) and are also detected in goats (29). We can speculate that these structures are made evident in older goats after at least one anestrus phase.…”
Section: Discussionmentioning
confidence: 85%
“…A sequence of capillary remodelation has been proposed in the follicle capillary network so that, in preovulatory follicles angiogenesis is commonly initiated by the outward growth of endothelial cells from preexisting vessels (budding), which is followed by sprouting (elongation) and dilation of the incipient new vessel. In contrast, in late periovulatory follicles infolding (intussusception) and duplication or splitting of preexisting vessels followed by sinusoidalization leads to a rapid neovascularization of the ovulated follicle so as to sustain the nutrition and function of the developing corpus luteum (Macchiarelli et al, ; Martelli et al, ; Miranda‐Moura et al, ; Mauro et al ). Similarly, in the uterus an effective neovascularization is observed during the endometrial proliferation occurring in the luteal phase of the estrous cycle or in the placenta (Rogers and Abberton, ; Huppertz and Peeters, ).…”
mentioning
confidence: 99%